Gender and Racial Differences in the Cardiovascular Risk Factors among Overweight and Obese Rural Adults, Kuching and Samarahan Division, Sarawak, Malaysia - Whye, Lian Cheah; Ching, Thon Chang; Helmy, Hazmi; Wan Manan, Wan Muda (Hindawi Publishing Corporation, 2016)
This study aimed to determine whether gender and ethnic differences had an effect on cardiovascular risk factors in overweight and obese rural adults in Sarawak. Design and Setting.This was a cross-sectional study conducted in rural communities in Kuching and Samarahan division,Malaysia. Data was obtained using a set of questionnaire (sociodemographic data and physical activity), measurement of blood pressure, height, weight (body mass index, BMI), body fat percentage, fasting blood sugar, and lipid profile from three ethnic groups—Iban, Malay, and Bidayuh. Analysis of data was done using SPSS version 23.0. Results. A total of 155 respondents participated in the study (81.6% response rate). The levels of physical activity, BMI status, body fat, hypercholesterolemia, and hyperglycemiawere similar across the three ethnic groups and both females andmales. Iban and Bidayuh had significant higher Atherogenic Index of Plasma (AIP) when compared to theMalay (BidayuhOR = 0.30, 95%CI 0.12, 0.78; Iban OR = 0.29, 95% CI 0.12, 0.69). Conclusions. The relationship between cardiovascular risk factors varied according to ethnic groups and gender. A better understanding of these differences would help in the design and implementation of intervention programme for the prevention of cardiovascular disease.